Pengaruh Return On Asset, Debt to Equity Ratio, Current Ratio dan Total Asset Turnover Terhadap Nilai Perusahaan (Studi Empiris pada Perusahan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2022) - Iqlima Ansori; Mia Laksmiwati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research is conducted to analyze of the Return on Asset, Debt to Equity Ratio, Current Ratio and Total Asset Turnover of Company Value, which proxied by Price to Book Value. The population in this research used secondary data in the form of financial reports from energy sector companies for the 2018-2022 period which were listed on the Indonesia Stock Exchange (IDX) as many as 76 companies. The research used a purposive sampling method and obtained 40 companies as sample. Data analysis used multiple linear regression analysis with help of the SPSS Version 25 program. The results of this research indicate that Return On Asset, Debt to Equity Ratio, Current Ratio and Total Asset Turnover have a positive and significant effect on company value.